Performance and healthcare analysis in elite sports teams using artificial intelligence: a scoping review - Munoz-Macho, A. A.; Dominguez-Morales, M. J.; Sevillano-Ramos, J. L. (Frontiers in Sports and Active Living, 2024)
Introduction: In competitive sports, teams are increasingly relying on advanced systems for improved performance and results. This study reviews the literature on the role of artificial intelligence (AI) in managing these complexities and encouraging a system thinking shift. It found various AI applications, including performance enhancement, healthcare, technical and tactical support, talent identification, game prediction, business growth, and AI testing innovations. The main goal of the study was to assess research supporting performance and healthcare.